The β3 Nicotinic Receptor Subunit: A Component of α-Conotoxin MII-Binding Nicotinic Acetylcholine Receptors that Modulate Dopamine Release and Related Behaviors - Cui, Changhai (J Neurosci, 2003)
Nigrostriatal dopaminergic neurons express many nicotinic acetylcholine receptor (nAChR) subunits capable of forming multiple nAChR subtypes. These subtypes are expressed differentially along the neuron and presumably mediate diverse responses. β3 subunit mRNA has restricted expression but is abundant in the substantia nigra and ventral tegmental areas. To investigate the potential role(s) of nicotinic receptors containing the β3 subunit in dopaminergic tracts, we generated mice with a null mutation in the β3 gene. We were thereby able to identify a population of β3-dependent α-conotoxin MII-binding nAChRs that modulate striatal dopamine release. Changes were also observed in locomotor activity and prepulse inhibition of acoustic startle, behaviors that are controlled, in part, by nigrostriatal and mesolimbic dopaminergic activity, respectively, suggesting that β3-containing nAChRs modulate these behaviors.